Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1029/93gl00088
|View full text |Cite
|
Sign up to set email alerts
|

Mean winds and tidal components during counter electrojet events

Abstract: The first observations of mean winds and the amplitude and phases of the tidal components measured with a meteor wind radar located at Trivandrum (8.5°N, 77°E) during five consecutive days of counter electrojet events identified in the horizontal component of the earth's magnetic field from January 27–31, 1987 are described. The mean zonal winds in the altitude region of 90–105 km are in general westward during counter electrojet days and eastward during no counter electrojet days. The amplitudes and phases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 17 publications
5
42
0
Order By: Relevance
“…Stening et al (1996) first suggested that there is an association between CEJ and high latitude stratospheric warming events. The reduction of diurnal tide amplitude on CEJ days was earlier reported by Somayajulu et al (1993) and later by using a large number of individual and groups of days by Sridharan et al (2002). Besides, Sridharan et al (2002) observed a clear anti-correlation between the semi-diurnal tidal amplitude and afternoon CEJ for the solstice months of June and July 1995.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Stening et al (1996) first suggested that there is an association between CEJ and high latitude stratospheric warming events. The reduction of diurnal tide amplitude on CEJ days was earlier reported by Somayajulu et al (1993) and later by using a large number of individual and groups of days by Sridharan et al (2002). Besides, Sridharan et al (2002) observed a clear anti-correlation between the semi-diurnal tidal amplitude and afternoon CEJ for the solstice months of June and July 1995.…”
Section: Discussionmentioning
confidence: 56%
“…They suggested that the solar semi-diurnal tides have a tendency to set up a westward electric field in the afternoon hours of the solstice season to cause a CEJ, unless this tendency is opposed by the diurnal tide. Somayajulu et al (1993) observed a westward excursion of background wind on CEJ days. They suggested that a combination of global tidal wind fields which tend to weaken the vertical polarization field in combination with local westward winds is necessary to produce the CEJ events.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, it has been suggested that the physical process of formation of CEEJ involves the local interaction of height varying zonal wind with the electrojet plasma, which can significantly modify the polarization electric field (Richmond, 1973;Stening, 1985). Somayajulu et al (1993) have shown that the zonal winds are considerably different on CEEJ and non-CEEJ days. We propose that the physical process involving formation of E sb and CEEJ are closely linked (Reddy and Devasia, 1981) winter (January-February, November-December).…”
Section: Discussionmentioning
confidence: 99%
“…For simulation of observed features of counter electrojet several theoretical models based on a combination of global scale tidal wind modes were suggested (Marriott et al, 1979;Hanuise et al, 1983). Recent experimental results carried out on a few consecutive CEJ days during January 1987 (Somayajulu et al,1993), provided evidence on the nature of zonal winds and amplitude and phase variations of tidal wind components during CEJ events. Thus considering that the Sq field in general is a function of the electrical conductivity of the dynamo region of the ionosphere and the tidal wind velocity, the time of Sq maximum as such depends on the contribution from these two factors.…”
Section: Discussionmentioning
confidence: 99%